Verification of Contractual Liability for Transmission of the Corona virus - Abdul-Qader, Dana Hama Baqy; Murad, Hero Abu-bekr Hma (Journal of Legal and Political Studies, 2022)
This research deals with an important effect of the Corona Virus (COVID 19) outbreak, which is the contractual responsibility of those who cause the transmission of this virus and infect the others. This issue requires having a contractual relationship between the person who causes the mistake of breaching this contract in transmitting the virus and the victim of the infection, as a result of the contractor’s mistake. Therefore, the research studies the elements and conditions of this responsibility, and it also argues the agreement to modify its effects in order to demonstrate the appropriateness of applying the general rules of contractual responsibility to the responsibility based on transmitting this Virus to others.
Keywords: Corona Virus COVID 19; contractual responsibility; transmission; victim of the infection; general rules of contractual responsibility